Structural, microstructural, and magnetic studies of Y3Fe5-xNixO12 garnet nanoparticles. Issue 13 (September 2020) - Agarwal, P.; Khanduri, H.; Link, J.; Stern, R.; Khan, S.A.; Garg, V.; Dimri, Mukesh C.
Abstract: This paper reports the structural and magnetic properties of a series of Y3 Fe5-x Nix O12 (x = 0, 0.05, 0.1, and 0.2) nanopowders synthesized by the citrate combustion method. We have discussed the change in different properties with the variation in calcination temperatures as well as the Ni ion substitution in yttrium iron garnet. X-ray diffraction study confirmed the desired garnet phase formation in all the calcined powders, and the crystallinity improved with an increase in calcination temperature. The crystallite sizes were observed in the range 47–52 nm and 84–94 nm for the samples calcined at 800 and 1000 °C, respectively. Scanning electron micrographs confirmed that the grains were in the nanometre range (132–170 nm) at 800 °C and increased (351–363 nm) at 1000 °C. Larger grains at high calcination temperature resulted in the enhanced saturation magnetization and a decrease in coercivity. Curie temperature (Tc ) was observed in the range 558–560 K for all the calcined Y3 Fe5-x Nix O12 samples. Nickel substitution for iron sites in Y3 Fe5-x Nix O12 decreased the saturation magnetization and enhanced the coercivity. This could be related to the substitution of Ni ions for tetrahedral iron sites, which changed the magnetic exchange interactions of different lattice sites. The magnetic anisotropy constant (K) increases with the enhancement of calcination temperature, whereas it decreases with nickel ion substitution in Y3 Fe5-x Nix O12 . This study suggests that the structural and magnetic properties can be tuned by Ni substitution for the Fe ions in Y3 Fe5 O12 garnets at different calcination temperatures, which make them promising candidates for various technological applications.